Identify the roles of customer relationship marketing In merchandising activities of Royal Footwear Limited - Islam, Md. Sazibul (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2017.